Teeth outside the mouth: The evolution and development of shark denticles. Issue 1 (3rd January 2023) - Cooper, Rory L.; Nicklin, Ella F.; Rasch, Liam J.; Fraser, Gareth J.
Abstract: Vertebrate skin appendages are incredibly diverse. This diversity, which includes structures such as scales, feathers, and hair, likely evolved from a shared anatomical placode, suggesting broad conservation of the early development of these organs. Some of the earliest known skin appendages are dentine and enamel‐rich tooth‐like structures, collectively known as odontodes. These appendages evolved over 450 million years ago. Elasmobranchs (sharks, skates, and rays) have retained these ancient skin appendages in the form of both dermal denticles (scales) and oral teeth. Despite our knowledge of denticle function in adult sharks, our understanding of their development and morphogenesis is less advanced. Even though denticles in sharks appear structurally similar to oral teeth, there has been limited data directly comparing the molecular development of these distinct elements. Here, we chart the development of denticles in the embryonic small‐spotted catshark ( Scyliorhinus canicula ) and characterize the expression of conserved genes known to mediate dental development. We find that shark denticle development shares a vast gene expression signature with developing teeth. However, denticles have restricted regenerative potential, as they lack a sox2 + stem cell niche associated with the maintenance of a dental lamina, an essential requirement for continuous tooth replacement. We compare developing denticles to other skin appendages, including both sensory skin appendages and avian feathers. This reveals that denticles are not only tooth‐like in structure, but that they also share an ancient developmental gene set that is likely common to all epidermal appendages. Abstract : The hatching‐stage (Stage 34) small‐spotted catshark ( Scyliorhinus canicula ) has a range of denticle morphologies that emerge during embryogenesis; from flattened cusps at the leading edge of the rostrum (magenta), to large rooted oval cusps of the dorsal row (green), and then thin, pointed body denticles on the trunk (blue). The schematic diagram shows expression of the denticle gene set; a molecular signaling cascade that regulates denticle development from placode stage to advanced morphogenesis, shared with vertebrate oral teeth. Highlights: Despite the structural similarity between shark denticles and oral teeth, their early development has not been comprehensively compared. We demonstrate that developmental gene expression patterns are broadly conserved between these units. We also describe a key distinction in the expression of sox2, observed during the development of shark teeth, but absent from developing denticles. This is indicative of the role of sox2 in maintaining the continuous replacement of shark teeth—a characteristic that is not exhibited by denticles.